Comparative Study of Poverty Alleviation in The Verses of The Qur’an and The Green Economy Program SGDS - Riwanda, Agus; Wafa, Ali (LP2M IAIN kUDUS, 2023)
Poverty is defined based on the failure of individuals to meet their primary life needs. Poverty has a tremendous negative impact on the life of the individual and community level. All societies in the world have made efforts to overcome this challenge. This study uses a qualitative approach by collecting verses related to poverty and presenting them in a categorization form to obtain an intervention level. Islam, through the Qur’an, has presented a comprehensive system to overcome this poverty problem. At the individual level, poverty can be reduced by providing aqidah concepts regarding sustenance, increasing skills and creativity, and encouragement to work hard while still paying attention to sustainability aspects. At the community level, the Qur’an recommends building a social welfare net through philanthropic movements and the spirit of altruism and stipulating religious obligations and suggestions regarding the distribution of wealth